Study of serum levels of CRP and procalcitonin as early marker of sepsis in children with sepsis above neonatal age group - Kumar, Vinaya; Neelannavar, Ramesh (International Journal of Contemporary Pediatrics, 2019)
Background: Sepsis caused by infection remains a major cause of mortality and morbidity among children. Blood culture though gold standard requires lot of time for diagnosis, hence it’s necessary to rely on early diagnostic markers such as blood counts, micro-ESR, CRP, Procalcitonin. The objective of this study is to evaluate the serum levels of CRP, Procalcitonin as reliable and as early marker of sepsis in pediatric patients above neonatal age group. Methods: Children aged above neonatal age group with clinically suspected sepsis as per the definition given by the International Paediatric sepsis Consensus Conference were selected. Patients were classified as those with sirs, sepsis, severe sepsis and septic shock. Patients were divided into two groups one with culture proven sepsis and the other with non-culture proven sepsis. All patients had CRP, Procalcitonin levels measured at admission and 24hrs after admission. The primary outcome was to determine reliable marker in differentiating between the culture proven and non-culture proven sepsis, and to determine the early marker of sepsis. Results: Total 104 patients formed the study group, of which 42 belonged to SIRS group, 26 were sepsis, 19 were severe sepsis and 17 were septic shock. A total of 36 cases had culture positive. In present study PCT was found to be more reliable marker of sepsis as the sensitivity and specificity of PCT was more than CRP and AUC for PCT was significantly higher than CRP. PCT was found to be early marker as the AUC for CRP at 24hrs was significantly more than AUC for CRP at admission and there was no statistically significant difference between AUC for PCT at admission and 24 hours after admission. Conclusions: Both CRP and PCT levels have favourable test performance but PCT is more reliable. PCT is earlier to rise compared to CRP.